The Effect of Work Motivation, Job Satisfaction, and Non-Financial Compensation of Employees on Organizational Commitment Case Study at PT BPR Brata Bhakti Sejahtera - Hendro Wibowo, Gunawan; Adriansyah, Ahmad; Maju Simatupang, Batara; Pracoyo, Antyo (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This research aims to examine the influence of work motivation, job satisfaction, and non-financial compensation on organizational commitment at PT BPR Brata Bhakti Sejahtera. Organizational commitment is one of the important factors in maintaining employee performance and loyalty in the long term. This study uses a quantitative method with a case study approach and involves 16 respondents who are BPR employees. Data testing was carried out using the chi-square test to determine the relationship between independent and dependent variables. The results of the study indicate that work motivation and non-financial compensation have a significant effect on organizational commitment, each with a significance value of 0.043 and 0.046 (p <0.05). This confirms that employees who have high motivation and receive adequate non-financial compensation such as awards, recognition, and opportunities for self-development tend to have high loyalty to the organization. Meanwhile, job satisfaction does not show a significant effect on organizational commitment, with a significance value of 0.130 (p>0.05). This finding indicates that in the banking context, employee commitment is more influenced by intrinsic motivation and non-material rewards than general job satisfaction.